Nursing Students’ Views on Numeracy: An Exploratory Cross-Sectional Study in Riyadh, Saudi Arabia - Alsufyani, Mashael (Asian Journal of Pharmaceutics (AJP), 2025)
Medication administration in healthcare settings demands strong mathematical skills from healthcare practitioners. This study investigated nursing students’ perceptions of mathematical calculations in Nursing at a Saudi university in Riyadh, Saudi Arabia. Materials and Methods: A cross-sectional study was conducted at the College of Nursing in a Saudi University, Riyadh, Kingdom of Saudi Arabia, between June and July 2025. The data were collected using a self-administered paper-based questionnaire of 16 items and analyzed using the statistical package for the social science (SPSS) version 26. Results: Among the students, majority were male, 74% (n = 182) belonged to the baccalaureate nursing program as compared to 20.3% (n = 50) in the Masters’ nursing program. Nearly 58% of participants claimed that they studied mathematics during their nursing course (n = 141). While 56.9% (n = 140) perceived that their ability to perform mathematical calculations related to drug dosing would be important to them as future practicing nurses. One-third of the students were perceived (n = 83) to have good skills, while only 23.6% (n = 58) had excellent mathematical skills. A significant association was found between participant characteristics, such as age (P < 0.0001), educational level (P < 0.0001), degree (P < 0.0001), and the rating of self-reported perceptions of mathematical ability (P < 0.0001). Conclusion: This study reveals that nursing students perceive mathematical skills positively and advocate for increased emphasis on medical calculations in their degree course. Furthermore, our findings underscore the importance of enhancing nursing students’ understanding of mathematical skills and their critical role in healthcare.